GEOGRAPHIC INFORMATION SYSTEMS (GIS) AS A VITAL TOOL IN HUMAN RIGHTS WORK - Syryt, Aleksandra (GIS Odyssey Journal, 2022)
In the face of various local, regional, and global threats, the protection of human rights develops and increases its importance. National and international legal acts define catalogues of human rights and create institutional and procedural conditions for their protection. However, apart from that, it is also necessary to use other tools that will support activities for the protection of human rights in various dimensions while respecting the law. Undoubtedly, one of such tools can be GIS. The potential of GIS is in providing information and responding to a threat, and locating the place and extent of human rights violations, which allows for an ex-post response. GIS can improve geographic literacy and improve our knowledge of where human rights violations are occurring. It can improve public awareness of human rights by placing them geographically. GIS can also support various projects aimed at the protection of human rights. Due to the topicality of the topic and the increase in phenomena affecting human beings and human rights, especially in the context of military operations, it is reasonable to deepen this issue and indicate the detailed scopes of GIS application in the service of human rights. The analysis will also identify the opportunities and risks associated with this tool in achieving human rights objectives.